A Rights‐Based Approach to Sexuality Education: Conceptualization, Clarification and Challenges. Issue 2 (1st May 2014) - Berglas, Nancy F.; Constantine, Norman A.; Ozer, Emily J.
<x xml:space="preserve">Abstract</x> Context Although a rights‐based approach to sexuality education has been increasingly discussed in the past decade, documented consensus regarding the goals, concepts and underlying assumptions of this approach is lacking. Differences in the assumed meaning of a rights‐based approach can limit discussions of its implementation and evaluation, and impede opportunities to explore and critique a new model for sexuality education. Methods In‐depth interviews were conducted in 2012 with 21 U.S. and international sexuality education experts. Data were thematically coded and analyzed using an iterative approach. Responses were compared according to respondents' professional discipline and geographic focus. Results A rights‐based approach can be defined as the intersection of four elements: an underlying principle that youth have sexual rights; an expansion of programmatic goals beyond reducing unintended pregnancy and STDs; a broadening of curricula content to include such issues as gender norms, sexual orientation, sexual expression and pleasure, violence, and individual rights and responsibilities in relationships; and a participatory teaching strategy that engages youth in critical thinking about their sexuality and sexual choices. These elements were consistently identified by respondents across professional disciplines and geographic foci. In addition, all respondents raised questions about the feasibility of implementing a rights‐based approach, particularly in the United States. Conclusions While questions remain to be answered regarding the implementation and impact of rights‐based sexuality education, the proposed conceptual definition suggests multiple avenues for advocates, researchers, program developers and funders to enhance adolescent sexual health.